Characterization of the evolution of post-COVID-19 syndrome in Cochabamba, Bolivia, 2020-2021 - Ortega Martinez, Rommer Alex (2023)
Objectives. To characterize the evolution of post-COVID-19 syndrome in Cochabamba-Bolivia, 2020-2021. Methods. Prospective, observational and analytical study. The sample consisted of 62 patients surveyed with COVID-19. Symptom severity and persistence were investigated. Fisher's exact test, calculation of the n coefficient, Kruskal-Wallis test, Mann-Whitney U, in addition to binary logistic regression were applied. Results. The mean age was 34.2 ± 11.6 years; dyspnea was present in 45% and cough with 42%; precordial pain with 30%; asthenia and myalgias with 29%; anxiety and depression with 47%, memory and concentration alteration with 24%; predominant risk factor obesity in 11%. Symptom evolution was for more than 10 days in 48%; hospitalization was between 1 to 7 days in 23 % of cases; a decrease in work performance was observedin 34%, in quality of life in 23% and economic affectation in 58%. Symptom persistence was present in 50%, correlated with hospitalization, decreased quality of life and baseline disease (p < 0.05); in addition, an OR: 4.87, 95% CI (1.54-17.2) was obtained for moderate symptoms and an OR: 4.42, 95% CI (1.28-17.6) for hospitalization in symptom persistence. Conclusions. The presence of young patients, mild and moderate symptoms and varied symptomatology stands out. The persistence of symptoms was related to hospitalization and moderate symptoms; we can suggest post-acute COVID-19 syndrome and chronic COVID-19 syndrome (< and > 12 weeks), as tentative defnitions, although more studies are still needed.